1991
DOI: 10.1088/0953-8984/3/27/016
|View full text |Cite
|
Sign up to set email alerts
|

Staggered flux phase and d-wave phase of the t-J model

Abstract: We have numerically evaluated the energy of the staggered flux phase state (sm), the d-wave resonating valence bond state, and the mixed SFP and d-wave state (sm + d) of the extended 1-3 model at various hole densities (6). The flux per plaquette and the size of the d-wave gap are taken as variational parameters. The calculation includes the kinetic energy, spinenergy, the effectivehole-holeinteraction and the three-sitepair-hoppingterm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They demonstrated that the recombination activity at room temperature of contamination-free GBs is weak and the GB structure has minor effect on the electrical GBs properties. They also studied the impact of the impurity contamination on the recombination activity of grain boundaries in mc-silicon cut from different solidification positions of a B-doped ingot [18,19]. The metallic impurities content in the samples studied, except for Fe, was under the detection limit.…”
Section: Role Of Grain Boundariesmentioning
confidence: 99%
“…They demonstrated that the recombination activity at room temperature of contamination-free GBs is weak and the GB structure has minor effect on the electrical GBs properties. They also studied the impact of the impurity contamination on the recombination activity of grain boundaries in mc-silicon cut from different solidification positions of a B-doped ingot [18,19]. The metallic impurities content in the samples studied, except for Fe, was under the detection limit.…”
Section: Role Of Grain Boundariesmentioning
confidence: 99%